Solid‐state Fluorescence from Carbon Dots Widely Tunable from Blue to Deep Red through Surface Ligand Modulation. Issue 12 (12th January 2023) - Ai, Lin; Song, Ziqi; Nie, Mingjun; Yu, Jingkun; Liu, Fukang; Song, Haoqiang; Zhang, Biao; Waterhouse, Geoffrey I. N.; Lu, Siyu
Abstract: Carbon dots (CDs) find widespread attention due to their remarkable fluorescent and electronic properties. However, aggregation‐caused quenching currently limits the application of CDs in colored displays. The construction of CDs with color‐tunable solid‐state fluorescence (SSF) is rarely reported, since the preparation of SSF CDs is technically challenging. Herein, through surface ligand modulation, SSF CDs with an emission‐color span of almost 300 nm (from blue to deep red) were obtained. In‐depth structure‐property studies reveal that intra‐ and inter‐molecular hydrogen‐bonding inside SSF CDs provokes the emission properties in the aggregated state. Photodynamic characterizations demonstrate emission wavelengths can be switched smoothly by deliberately altering conjugation ability between substituent ligands and CDs core. Three‐dimensional printing patterning is used to create a range of emissive objects, demonstrating the commercial potential for use in optical lamps. Abstract : Solid‐state fluorescent (SSF) carbon dots (CDs) with an emission‐color span of almost 300 nm (from blue to deep red) were obtained through surface ligand modulation. The emission wavelengths can be switched smoothly by deliberately altering the conjugation ability between substituent ligands and carbon core. The developed SSF CDs showed great potential for widespread use in three‐dimensional printing and various types of optical displays.